PERANAN KINERJA PENGELOLAAN OBYEK WISATA â€œKEBUN RAYA UNIVERSITAS MULAWARMAN SAMARINDAâ€ SEBAGAI PELAYANAN KEPADA PUBLIK - zainuddin, meirinda rizqi (ADMINISTRASI PUBLIK, 2018)
Based on data of productivity statistics in document management in General and Officers Division of Regional Secretariat of East Kutai Regency increased. To handle the increasing demands for document processing, a high work spirit and work ethic are required. In this thesis discussed The Effect of Employee Morale Work Productivity At The General and Officer Division of Regional Secretariat of East Kutai Regency. Against Productivity Document Management In this thesis will be analyzed whether there is influence between employee morale with the productivity of document management using Product Moment Correlation (Pearson).After the authors analyze the data and conduct hypothesis testing, both to employee morale variable (X) and productivity variable (Y), it can be concluded that employee morale variable has a positive effect on productivity in document management. It can be proven from the results of data analysis using Product Moment Correlation (Pearson) obtained correlation coefficient r = 0.86. Where in the interpretation criteria in table 1, that is 0.80 to 0.100 is the level of relationship (correlation) is very strong. This means the higher employee morale Against Work Productivity in the General and Officer Division of the Regional Secretariat of East Kutai Regency, the higher the productivity in document processing